2005
DOI: 10.1287/isre.1050.0045
|View full text |Cite
|
Sign up to set email alerts
|

Post-Adoption Variations in Usage and Value of E-Business by Organizations: Cross-Country Evidence from the Retail Industry

Abstract: G rounded in the innovation diffusion literature and the resource-based theory, this paper develops an integrative research model for assessing the diffusion and consequence of e-business at the firm level. Unlike the typical focus on adoption as found in the literature, we focus on postadoption stages, that is, actual usage and value creation. The model thus moves beyond dichotomous "adoption versus nonadoption" and accounts for the "missing link"-actual usage-as a critical stage of value creation. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
1,076
12
27

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,227 publications
(1,165 citation statements)
references
References 65 publications
50
1,076
12
27
Order By: Relevance
“…It has been applied to understand the adoption of many IS applications or technologies such as interorganizational systems, e-business, electronic data interchange, open systems, and enterprise systems. However, each study used slightly different factors as measures for each of the framework's dimensions [5], [73], [83]. In addition, according to Table 1, it can be demonstrated that in order to explain the adoption of several diverse IS innovations; TOE framework can successfully be utilized.…”
Section: Technology-organization-environment Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been applied to understand the adoption of many IS applications or technologies such as interorganizational systems, e-business, electronic data interchange, open systems, and enterprise systems. However, each study used slightly different factors as measures for each of the framework's dimensions [5], [73], [83]. In addition, according to Table 1, it can be demonstrated that in order to explain the adoption of several diverse IS innovations; TOE framework can successfully be utilized.…”
Section: Technology-organization-environment Frameworkmentioning
confidence: 99%
“…In addition, according to Table 1, it can be demonstrated that in order to explain the adoption of several diverse IS innovations; TOE framework can successfully be utilized. Likewise, the TOE model was applied and tested in Asian, European, and American, in addition to both developed and developing countries [73], [83][84][85]. To all intents and purposes, the experts generally agree on the three TOE dimensions suggested by Tornatzky and Fleischer [76], including the effect of environment, organization and technology adoption.…”
Section: Technology-organization-environment Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The TOE theory has been used by a large number of studies to investigate the adoption of, for example, Electronic Data Interchange (EDI) (Kuan and Chau, 2001), open systems (Chau and Tam, 1997), and e-business (Zhu and Kraemer, 2005). The main contribution of TOE is that it encourages the researcher to take the broader context into account in which innovation takes place.…”
Section: Technology-organization-environment (Toe) Theorymentioning
confidence: 99%
“…Following what Zhu and Kraemer (2005) have suggested, we mainly focus on the financial aspect of commitment which refers to the commitment of financial resources to Green IT as a proportion of total organizational resources. In the particular context of Green IT, we tend to adopt and tailor such measurable indicators as Green IT operating budget as percent of total revenue and Green IT spending as percent of total revenue as recommended by Zhu and Kraemer (2005) to denote the degree to which the financial aspect of commitment represents overall organizational resources. The literature of IS adoption and innovation has indicated that financial resources is another important antecedent to IS diffusion (Iacovou et al, 1995;Ramamurthy et al, 1999;Zhu and Kraemer, 2005).…”
Section: Organizational Contextmentioning
confidence: 99%